Effectiveness of Matricaria chamomilla Essential Oil on Aggregatibacter actinomycetemcomitans and Treponema denticola Biofilms - Nurrahman, Hana Fauziyah; Widyarman, Armelia Sari (Indonesian Dental Association, 2020)
Introduction: Matricaria chamomilla (chamomile) is known to possess antimicrobial, anti-inflammatory, and antioxidant properties. Objectives: The purpose of this study was to determine how effectively Matricaria chamomilla essential oil acts against Aggregatibacter actinomycetemcomitans and Treponema denticola biofilms in vitro. Methods: Aggregatibacter actinomycetemcomitans ATCC-29522 and T. denticola ATCC-35405 were separately cultured in brain heart infusion (BHI) broth at 37°C for 2 4h in anaerobic conditions. Each bacterial suspension (200 uL, 107 CFU/mL) was cultured in 96-well plates for 48 h to form a biofilm. Thereafter, biofilms were treated with chamomile essential oil at concentrations of 3.12%, 6.25%, 12.5%, 25%, 50%, and 100% in a time-dependent experiment. Readings were taken at 1 h, 3 h, 6 h, and 24 h. Biofilm mass was evaluated using crystal violet staining (for A. actinomycetemcomitans) and safranin staining (for T. denticola). Biofilms treated with chlorhexidine (0.2%) and untreated biofilms were used as positive and negative controls, respectively. Data were statistically analyzed using one-way analysis of variance (ANOVA), with the significance level set to p<0.05. Results: Chamomile essential oil significantly reduced the biomass of the biofilms (p<0.05). The most effective chamomile oil concentrations for inhibiting A. actinomycetemcomitans and T. denticola biofilms were 100% and 50%, respectively, with 24 h incubation periods. The results of ANOVA and the post hoc Least Significant Difference (LSD) test showed a significant reduction (p<0.05) in biofilm mass for all concentrations of chamomile essential oil compared to the negative control across all incubation times. Conclusion: The data suggest that chamomile essential oil can inhibit the biofilm formation of A. actinomycetemcomitans and T. denticola biofilms. It could, therefore, be useful as an alternative treatment to inhibit the biofilms composes of the bacteria tested in periodontal disease cases. However, continued researches are necessary to further explore the mechanisms of this effect.